Visceral adiposity index and its association with Dietary Approaches to Stop Hypertension (DASH) diet scores among older adults: National Health and Nutrition Examination Surveys 2011–2014. Issue 6 (June 2021) - Ferguson, Christine C.; Knol, Linda L.; Ellis, Amy C.
Summary: Background & aims: The visceral adiposity index (VAI) has been shown to be a reliable estimate of visceral adiposity, but little is known about its association with specific dietary patterns such as the Dietary Approaches to Stop Hypertension (DASH) diet, particularly in older adults. Many studies have shown the DASH diet to be beneficial for cardiometabolic health. The purpose of this study was to investigate the relationship between DASH diet scores and the VAI in older adults using a nationally representative dataset. Methods: Using the National Health and Nutrition Examination Surveys (NHANES) from 2011 to 2014, data from 508 community-dwelling older adults were examined, and dietary intake was evaluated using the Dixon's DASH diet index. Using multiple linear regression analysis, the relationship between VAI and DASH diet score was assessed while controlling for demographic variables. Results: Participants' average DASH diet score was 2.41 (SE = 0.07), and the average VAI was 1.55 (SE = 0.08). The results suggest a significant inverse relationship between the DASH diet and VAI ( β  = −0.19, t  = −2.73, p  = 0.009). Conclusions: Results of this study suggest that protective properties of the DASH diet pattern may be due in part to its inverse relationship with visceral adiposity. This information supports practitioners' use of the VAI with older adults in addition to providing nutrition counseling with the DASH diet to reduce patients' cardiometabolic risk. Highlights: Higher DASH diet scores may be protective against visceral adiposity in older adults. Visceral adiposity in older adults may differ by sociodemographic characteristics. The Visceral Adiposity Index can easily be calculated using clinical data.